Developing the aquaticity level in healthy adolescents. A randomized control study - Varveri, Danae; Karatzaferi, Christina; Polatou, Elizana; Sakkas, Giorgos K. (Frontiers in Sports and Active Living, 2024)
Aquaticity is an important parameter of human aquatic performance and behavior and can be objectively assessed by the aquaticity assessment test. Low aquaticity score can unveil a person's high risk in the water while it could dictate the specific characteristics that need to be addressed or developed for improving water competence.The aim of the current study was to assess whether human aquaticity can be developed by systematic exercise and which type of training is more effective in improving aquaticity score.: Twenty healthy untrained, high school students (8M/12F, 16.5±0.7) participated in the study after obtaining parental consent. Participants were screened for their aquaticity level using the Aquaticity Assessment Test (AAT) and randomly divided into two groups: Group A (4M/6F, 16.3±0.8) completed a classical swimming training program, while Group B (Aquaticity) (4M/6F, 16.8±0.5) completed the aquaticity intervention program. Both interventions lasted for two months (3 workouts/ per week, lasting 60 min per session) while participants assessed before and after the training period using the same testing protocol and evaluators.Results: Aquaticity score was improved after training by 13% (13.23 ± 6.88%) for Group A (Swimming training) and 26% (-26.6 ± 10.40%) for Group B (Aquaticity training) (p=0.004). In Group A (swimming), 7 out of 10 tasks were improved significantly compared the pre-values (p<0.05) while in Group B (aquaticity) 10 out of 10 shown significant improvements compared to pre-training values. Interestingly, the magnitude of change between the two groups was statistically significant in 5 out of 10 tasks (tasks 2, 3, 7, 9, 10) implying a higher magnitude of improvements in the aquaticity intervention group compare to swimming group.Discussion: Aquaticity can be developed and improved when a specific training program applied. Essential to water competence aquaticity skills can be advanced using simple aquaticity training games that can improve water confidence and reduce drowning related accidents.